ANALISIS HUBUNGAN BEBAN KERJA MENTAL DENGAN STRES KERJA DI INSTALASI CSSD RUMAH SAKIT UMUM HAJI SURABAYA - Dikky Fahamsyah (Universitas Airlangga, 2017)
ABSTRACT Mental workload is a workload which is the difference between the demands of the workload of a task with a maximum capacity load of a person's mental condition motivated, excessive workload will lead to the incident of stress. Work stress is distress experienced by employees when facing job. The purpose of this research was to study the picture of mental workload and stress on employees who work in CSSD Installation General Hospital Haji Surabaya. This research was a descriptive cross sectional approach. The subjects of this research were employees in the Installation CSSD General Hospital Haji Surabaya. The variables of this research were the mental workload and job stress. Primary data was collected using questionnaires and observation. Secondary data obtained from the General Hospital Haji Surabaya. Furthermore the data was processed by descriptive and described in narrative form. The results showed that the CSSD employees experiencing mental workload which was divided into seven employees experiencing medium metal workload and four employees experiencing low mental workload . In addition there was a relationship between mental workload with the incidence of workplace stress. overall it can be described that mental workload and workplace stress were in the medium level. It was recommended that employees can used the time off well and getting used to exercise to increase endurance. Keywoard : mental workload, workplace stress, installation sterilization center